2022
DOI: 10.3389/fchem.2022.815991
|View full text |Cite
|
Sign up to set email alerts
|

Uncover New Reactivity of Genetically Encoded Alkyl Bromide Non-Canonical Amino Acids

Abstract: Genetically encoded non-canonical amino acids (ncAAs) with electrophilic moieties are excellent tools to investigate protein-protein interactions (PPIs) both in vitro and in vivo. These ncAAs, including a series of alkyl bromide-based ncAAs, mainly target cysteine residues to form protein-protein cross-links. Although some reactivities towards lysine and tyrosine residues have been reported, a comprehensive understanding of their reactivity towards a broad range of nucleophilic amino acids is lacking. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…A similar analysis involving the nearest LC/A nucleophile revealed that crosslinking only occurred with Cα–Cα distances between 8–10 Å, although not all mutants with a nucleophilic residue at this distance showed evidence of spontaneous crosslinking (Figure S8b). Since alkyl halides have been shown to react with diverse nucleophiles present in proteins, , we also systematically examined the Cα distances to each type of reactive nucleophile in LC/A (Figure S8c). No discernible correlation was observed between crosslinking and distance for most nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…A similar analysis involving the nearest LC/A nucleophile revealed that crosslinking only occurred with Cα–Cα distances between 8–10 Å, although not all mutants with a nucleophilic residue at this distance showed evidence of spontaneous crosslinking (Figure S8b). Since alkyl halides have been shown to react with diverse nucleophiles present in proteins, , we also systematically examined the Cα distances to each type of reactive nucleophile in LC/A (Figure S8c). No discernible correlation was observed between crosslinking and distance for most nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…E) KEGG analysis of Trx1 interacting proteins from this study. Comparison of identified cross-linked peptides and interacting proteins from this study with those identified using an unnatural amino acid BprY (F) [ 29 ], disulfide trapping(G) [ 5 ], and SNO (H) [ 30 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified 121 cross-linked peptides by incorporating genetically encoded unnatural amino acid BprY onto residue 33 of Trx1 [ 29 ], leading to the discovery of 87 interacting proteins. The study here covered ∼32% BprY cross-linked peptides and ∼48% BprY cross-linked proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among those, bromoalkane‐ncAAs have been reported to also target, besides the preferred Cys residue, the primary amine of Lys, the imidazole of His, and the acid group of Glu and Asp. A recent comprehensive analysis of the reactivity of BrPrY ( 11a ) based on the mass spectrometric characterization of crosslinking products has added to the list the alcohol group of Ser, Thr, Tyr (Shu et al, 2022 ). An interesting ncAA targeting Cys is ThioD ( 14 ), which carries on the side chain a thioester suitable for chemical ligation (Xuan et al, 2018 ).…”
Section: Genetically Encoded Chemical Crosslinkersmentioning
confidence: 99%